Estudio de factibilidad para establecer un restaurante con zona de esparcimiento en el sector de portalegre (2022)
The feasibility study project is carried out, to provide the inhabitants of the area with an innovative restaurant, where they can get out of the routine without increasing their expenses and improving their quality of life. The need of the families of the Hogares Soacha sector to have a closer road to get to the center of Soacha and the highway, motivated its inhabitants to build a bridge for the benefit of this community, which increased the traffic of people in the Portalegre sector. With the supply of housing that the municipality of Soacha has, the population of the municipality has increased, it is evident the lack of supply in businesses to cover the insufficiencies of the thousands of families that now live in this area. In the sector in which the feasibility study is focused, a market study was carried out to identify the demand in the sector, the technical part is established and an economic study is carried out